2004
DOI: 10.1002/mabi.200400009
|View full text |Cite
|
Sign up to set email alerts
|

Fully‐Biodegradable Poly(3‐hydroxybutyrate)/Poly(vinyl alcohol) Blend Films with Compositional Gradient

Abstract: Fully-biodegradable bacterial poly(3-hydroxybutyrate) (PHB)/chemosynthetic poly(vinyl alcohol) (PVA) blend films with compositional gradient from one surface to the other surface of the films were prepared by a dissolution-diffusion technique. Three kinds of PVA samples, high- and low-molecular weight atactic PVA and highly syndiotactic PVA (s-PVA), were used in order to investigate the effects of molecular weight and tactic structure on the generation of compositional gradient. The solution of PHB in 1,1,1,3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 22 publications
1
19
0
1
Order By: Relevance
“…Increasing the antifoulant loading to 10% (w/w) DCOI prevented re-crystallisation (Figure 2b). This trend is consistent with reports of PHB blended with similar compounds such as poly(ethylene glycol) or poly(vinyl alcohol) where re-crystallisation is retarded [30], [31]; crystallisation temperatures for P(HB- co -8HV)-DCOI composites were seen, but up to 4°C lower (Figure 2d, Table 1). …”
Section: Resultssupporting
confidence: 91%
“…Increasing the antifoulant loading to 10% (w/w) DCOI prevented re-crystallisation (Figure 2b). This trend is consistent with reports of PHB blended with similar compounds such as poly(ethylene glycol) or poly(vinyl alcohol) where re-crystallisation is retarded [30], [31]; crystallisation temperatures for P(HB- co -8HV)-DCOI composites were seen, but up to 4°C lower (Figure 2d, Table 1). …”
Section: Resultssupporting
confidence: 91%
“…[12] However, it is well known that most of the biodegradable polymer blends are immiscible because of their chemical structures and high molecular weights. [13] Previous research, [9,10] including our own, [11] on functionally graded polymeric materials have focused mainly on miscible blend systems and several preparation techniques have been developed, while only a few groups have reported on the gradient morphology being obtained in immiscible blend systems. Xie et al reported that a gradient structure was formed between an immiscible polymer blend of polypropylene-co-poly(ethylene vinylacetate) (weight ratio, 70/30) by making use of their segregation behavior in the annealing process.…”
Section: Introductionmentioning
confidence: 99%
“…[13] First, 8 ml well mixed chloroform solution containing PEO/PHB20 was poured into a PTFE dish. The solution was evaporated at room temperature until the weight of the residual solution was 10% of the original solution weight, and then about 2 ml well mixed chloroform solution containing PEO/PHB50 was poured into the dish and evaporated.…”
Section: Preparation Of Blend Films and Gradient Filmsmentioning
confidence: 99%
“…In our previous work, [13] poly(3-hydroxybutyrate) (PHB)/poly(vinyl alcohol) (PVA) blend films with compositional gradient were analyzed by FT-IR microspectroscopy. Through the change of paired IR absorbance, we could monitor qualitatively the compositional distribution of PHB and PVA along the thickness direction of the blend films.…”
Section: Introductionmentioning
confidence: 99%